A novel water-stable luminescent metal complex exhibiting high sensitive and selective detection to Fe3+ and Al3+. (15th March 2021) - Xu, Ruixue; Wu, Qiong; Xing, Chang; Wang, Hongfei; Xu, Wenjuan; Meng, Xiangru; Hou, Hongwei
Graphical abstract: A tetraphenyl ethylene-based zinc complex with strong fluorescence properties and good water stability has been elaborately designed and synthesized. The complex is very sensitive to Fe 3+ and Al 3+ ions in water with detection limits of 0.31 μM and 0.913 μM, respectively. Highlights: A tetraphenyl ethylene-based zinc complex was designed and synthesized. The complex can be used as an excellent fluorescence probe to detect Fe 3+ and Al 3+ . Compared with other reported complexes, this probe has a lower detection limit. Abstract: The application of metal complexes as fluorescent sensor materials has attracted great attention. In this work, we designed and synthesized a tetraphenyl ethylene-based zinc complex [ZnLCl]·H2 O n (1 ), which not only has excellent water stability, but also shows good photoluminescence behavior. These properties endow 1 a good fluorescence detection ability to metal ions. The experimental results also confirm that the fluorescence behavior of 1 can be quenched by Fe 3+ or Al 3+ rapidly and sensitively. When other metal ions coexist with Fe 3+ or Al 3+, 1 can still effectively recognize Fe 3+ or Al 3+ . It means that 1 is a potential fluorescent sensor material with super anti-interference ability to detect Fe 3+ or Al 3+ . The reason is that there are weak interactions between Fe 3+ /Al 3+ and oxygen atoms in 1 . Since there's the competitive absorption between Fe 3+ and 1, the quenching effect coefficient of Fe 3+ is larger than that of Al 3+ and the quenching effect is better than that of Al 3+ .